Ações de educação nutricional em Unidades Básicas de Saúde da Família do interior de São Paulo e sua importância para a Promoção da Saúde - Ferro, Élen Lúcia Bagatini Saud (2021)
Introduction: nutritional care developed in primary health care, when strengthened and qualified, can be a more economical, quick and efficient way to promote the prevention of obesity and other Chronic Non-Communicable Diseases associated with poor diet. The Basic Health Units, especially the Basic Family Health Units, are the ideal places for the development of guidance and educational practices on healthy eating, as they empower the individual, making him into a protagonist in the care of his health. Objectives: to evaluate the anthropometric changes in eating habits and level of knowledge about healthy eating in adults who use two Basic Family Health Units, one corresponding to the control group, after a period of nutritional intervention. Methodological procedure: this is a longitudinal, quasi-experimental, quantitative, descriptive and interventional field research, which had as its target audience 224 users aged between 18 and 60 years, registered in two Basic Family Health Units from the interior of São Paulo, who were responsible for food acquisition in their homes. One of the units, whose research group consisted of 110 individuals, served as a control group; in the other, a nutritional intervention was carried out for approximately six months with 114 people. The research was divided into three phases: in the first, an initial analysis of the level of knowledge about healthy eating among users of the two units, their eating habits and anthropometric assessment was performed. In the second phase, nutritional education activities were developed in only one of the institutions; in the third, the same questionnaires from the first phase and the anthropometric evaluation were applied again in both units, to compare the data from the institution with intervention with those from the other one and to assess the effectiveness of the developed actions. In the control group unit, only phases one and three were performed. Data collection was performed with the help of properly trained students from the Nutrition course. Results: three articles were obtained: in the first, the profile of users in the two locations was traced and high rates of overweight, predominance of moderate knowledge and high consumption of processed and ultraprocessed products were verified in both units; in the second, the analysis of the results obtained only in the institution where the intervention took place was performed, obtaining considerable improvement in all analyzed items after the intervention period; and in the third, the results of the unit with intervention were compared with those of the unit that served as a control group, and in the first one, anthropometric enhancement was obtained, as well as improvement in the quality of food and in the level of knowledge about healthy eating. In the unit without intervention, there was little variation in weight loss and in the improvement of the level of knowledge, as well as a worsening in food quality, with the increase in the consumption of processed and ultraprocessed foods, especially among obese individuals. Final considerations: the effective and continuous participation of the nutritionist in primary care and the development of Food and Nutrition Education actions can only contribute to the improvement of the population's health and quality of life, as demonstrated by the results obtained in the study. Keywords: Food and nutrition education. Primary health care. Health promotion.